Novel electrohydrodynamic preparation of porous chitosan particles for drug delivery. - Pancholi, K; Ahras, N; Stride, E; Edirisinghe, M (2009)
Uniform spherical chitosan particles of size <10 microm in diameter are important in drug delivery applications due to their excellent biocompability and biodegradability. A high concentration of chitosan in the particles can help to control the release of drugs and methods for processing high viscosity chitosan solutions are therefore required. In principle, any type of polymer, whether hydrophobic or hydrophilic, can be electrosprayed to obtain monodisperse particles of diameter <10 microm. In practice, however, electrospraying of biopolymers having viscosities of >100 mPa s results in particles >10 microm diameter. In this study, by reducing surface tension of a high viscosity chitosan suspension, it was found that smaller diameter particles could be prepared. Chitosan solutions were electrosprayed in the stable cone-jet mode to systematically study the relationship between particle diameter, viscosity and surface tension. Increasing viscosity resulted in larger diameter particles with a broad size distribution, but decreasing surface tension had the opposite effect. Results show that a chitosan solution having a viscosity of approximately 80 mPa s can be used to prepare chitosan particles of diameter approximately 2.5 microm which on drying reduced to particles of 500 nm.